2022
DOI: 10.1098/rsob.220198
|View full text |Cite
|
Sign up to set email alerts
|

NDUFS3 knockout cancer cells and molecular docking reveal specificity and mode of action of anti-cancer respiratory complex I inhibitors

Abstract: Inhibition of respiratory complex I (CI) is becoming a promising anti-cancer strategy, encouraging the design and the use of inhibitors, whose mechanism of action, efficacy and specificity remain elusive. As CI is a central player of cellular bioenergetics, a finely tuned dosing of targeting drugs is required to avoid side effects. We compared the specificity and mode of action of CI inhibitors metformin, BAY 87-2243 and EVP 4593 using cancer cell models devoid of CI. Here we show that both BAY 87-2243 and EVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Metformin, an antidiabetic drug that has anti-proliferative activities through multiple mechanisms dependent and independent of complex I inhibition, did not impair tumour growth when administered at a high dose. This might be because metformin is less potent and specific than IACS-010759 38 , in some cellular models, it induces apoptosis at concentrations at which complex I is not fully inhibited 38 , suggesting that its previously reported antitumour effects may also result from the inhibition of other targets.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin, an antidiabetic drug that has anti-proliferative activities through multiple mechanisms dependent and independent of complex I inhibition, did not impair tumour growth when administered at a high dose. This might be because metformin is less potent and specific than IACS-010759 38 , in some cellular models, it induces apoptosis at concentrations at which complex I is not fully inhibited 38 , suggesting that its previously reported antitumour effects may also result from the inhibition of other targets.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the Q site performed with MOLEonline showed that the Q site assumes different shapes depending on the conformation of the CI itself and on the bound molecule(s). 50 The results of the docking calculations are reported in Figure 7 , while an analysis of the IDB interactions in the Q site is reported in Figure S9 . In the WT and mutant protein, the best IDB binding pose is located in proximity of the so-called shallow site, which is at the entrance of the Q-binding site, with the aromatic head of the molecule oriented toward the inside of the protein and in the proximity of Arg77 (PSST/NDUFS7).…”
Section: Resultsmentioning
confidence: 99%
“… 71 , 72 Re-docking calculations were conducted as described before. 50 The docking calculations were performed by using AutoDock Vina 1.0 73 with default parameters and generating 200 binding poses. The analysis of the results was made by using UCSF Chimera and LigPlot 4.5.3.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Blandino et al [42] implicated mir33a and c-Myc in the anticancer effects of metformin in breast cancer. More recently, Kurelac et al [43] demonstrated that metformin decreases proliferation and induces apoptosis in cancer cells devoid of complex I. Complicating matters, the concentration of metformin used to inhibit complex I in vitro (millimolar) differs from the micromolar concentrations observed in patient plasma [44].…”
Section: Metformin Targets Energy Metabolism In Cancer Cells and Immu...mentioning
confidence: 99%